Estimation of breed composition of South African sheep affected with wet carcass syndrome - Kooverjee, Bhaveni B.; Van Der Nest, Magrieta A.; MacNeil, Michael D.; Scholtz, Michiel M.; Neser, Frederick W. C.; Soma, Pranisha (Frontiers in Genetics, 2025)
Wet carcass syndrome (WCS), a condition that negatively affects the quality of carcasses after slaughter, is seriously threatening the South African sheep industry. Despite its economic impact, the underlying genetic mechanisms of WCS remain unknown. Initially, WCS was predominantly observed in Dorper sheep, leading to speculation that the condition was breed-specific. However, recent reports indicate WCS has occurred in various sheep breeds. This study aimed to determine whether WCS is breed-specific and whether breed composition influences its incidence. Meat samples from 164 WCS-affected and 83 unaffected sheep were collected and genotyped using the Ovine 50K SNP Bead Chip. Principal Component Analysis (PCA) and ancestry matrix assessments revealed that WCS-affected and unaffected sheep belonged to different commercial breeds. Additionally, crossbred animals were affected. These findings suggest that WCS is strongly associated with breed and that Dorper and Merino-types show heightened susceptibility. The genetic diversity of the affected animals suggests a multifactorial etiology, potentially involving environmental and managerial factors. Future studies should also explore the physiological mechanisms underlying WCS, including metabolic and stress-related pathways, to develop effective prevention strategies.